Q: What is 10 -3 -2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Here are possibilities of what you mean: a: (3-2)(x-2)=10 Solution: (3-2)(x-2)=10 1(x-2)=10 x-2=10/1 x=10+2=12 b: 3-2(x-2)=10 Solution: 3-2(x-2)=10 3-10=2(x-2) -7=2x-4 -3=2x x=-3/2=-1.5

10 - 3 + 2 = 2 is a false statement. 10 - 3 + 2 = 9

2/3 ÷ 3/10 = 2/3 × 10/3 = 20/9 = 2 2/9

6*10^9 / 2*10^3 = (6/2) * 10^9 / 10^2 = 3*10^(9-3) = 3*10^6 or 3 million.

3*x^2 + 2*x (where x=10)substitute 10 everywhere you see x. 3*(10^2) + 2*10 = 3*100 + 2*10 = 320

Related questions

2/5 - 3/10 = (2×2)/(5×2) - 3/10 = 4/10 - 3/10 = (4-3)/10 = 1/10.

Here are possibilities of what you mean: a: (3-2)(x-2)=10 Solution: (3-2)(x-2)=10 1(x-2)=10 x-2=10/1 x=10+2=12 b: 3-2(x-2)=10 Solution: 3-2(x-2)=10 3-10=2(x-2) -7=2x-4 -3=2x x=-3/2=-1.5

2/3 of 10 = 10*2/3 = 6.66...

3 - 2/10 = 2 and 8/10

10 - 3 + 2 = 2 is a false statement. 10 - 3 + 2 = 9

2/3 ÷ 3/10 = 2/3 × 10/3 = 20/9 = 2 2/9

6*10^9 / 2*10^3 = (6/2) * 10^9 / 10^2 = 3*10^(9-3) = 3*10^6 or 3 million.

1+2+3+4 = 10 ---------------------- For this question there is actually a whole lot of answers... for example: ((1 ＋ 2) ＋ 3) ＋ 4 ＝ 10 ((1 × 2) × 3) ＋ 4 ＝ 10 (1 ＋ 2) ＋ (3 ＋ 4) ＝ 10 1 ＋ (2 ＋ 3) ＋ 4 ＝ 10 1 × (2 × 3) ＋ 4 ＝ 10 1 ＋ ((2 ＋ 3) ＋ 4) ＝ 10 1 × ((2 × 3) ＋ 4) ＝ 10 1 ＋ (2 ＋ (3 ＋ 4)) ＝ 10 ((1 ＋ 2) ＋ 4) ＋ 3 ＝ 10 (1 ＋ 2) ＋ (4 ＋ 3) ＝ 10 So Manny Diffrent way's you can use four numbers to equal 10.

10 + 3 × 2 = 10 + (3 × 2) = 10 + 6 = 16

10.666667 = 10 and 2/3 10 and 2/3 = ((3 x 10) + 2) /3 = 32/3

It is 2 and 3/10.

2/5 - 3/10 = 4/10 - 3/10 = 1/10